Answer:
this answer is going to a 20 out of 100 percent
the answer is C or D
Write as a multiplication sentence.
5/6 divided by 1 1/2
Remember that
1 1/2=1+1/2=3/2
so
Answer:
-26
Step-by-step explanation:
well add the negative numbers first so you get
-17-18=(-35)
then you add 9 so its (-35)+9=26
Answer: (6a + 5b) • (6a - 5b)
Reformatting the input :
Changes made to your input should not affect the solution:
(1): "b2" was replaced by "b^2". 1 more similar replacement(s).
Step by step solution :
Step 1 :
Equation at the end of step 1 :
(36 • (a2)) - 52b2
Step 2 :
Equation at the end of step 2 :
(22•32a2) - 52b2
Step 3 :
Trying to factor as a Difference of Squares :
3.1 Factoring: 36a2-25b2
Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)
Proof : (A+B) • (A-B) =
A2 - AB + BA - B2 =
A2 - AB + AB - B2 =
A2 - B2
Note : AB = BA is the commutative property of multiplication.
Note : - AB + AB equals zero and is therefore eliminated from the expression.
Check : 36 is the square of 6
Check : 25 is the square of 5
Check : a2 is the square of a1
Check : b2 is the square of b1
Factorization is : (6a + 5b) • (6a - 5b)
Final result :
(6a + 5b) • (6a - 5b)
brainly would epic!
So it is an isosceles triangle that means that the bottom two angles are equal...
so
40 = 5x
divide both sides by 5 and you get 8
now the triangle angles add up to 180
we make an equation out of it...
(2y + 20 ) + ( 5(8)) + 40 = 180
2y + 20 + 40 + 40 = 180
combine like terms
2y + 100 = 180
so subtract 100 from both sides
2y = 80
divide by 2 to isolate the variable
y = 40
You are correct!!! :)